Richard A. Ballinger papers at the University of Washington Libraries - Ballinger, Richard Achilles, 1858-1922 (University of Washington Libraries, 1965)
Papers relating chiefly to Ballinger's term as U.S. Secretary of the Interior (1909-1911). Also includes materials pertaining to his service as Commissioner of the General Land Office (1907-1908). Documents the Ballinger-Pinchot controversy which resulted in a congressional investigation of the Interior Department and the Forestry Service in 1910.